Intrauterine transmission of COVID-19 in Pregnancy: case report and review of literature - Elkafrawi, Deena; Joseph, Julie; Schiattarella, Antonio; Rodriguez, Brian; Sisti, Giovanni (Acta Biomedica Atenei Parmensis, 2020)
We report the first case of SARS-CoV-2 pregnancy in the U.S. Our literature review highlights the rarity of COVID-19 intrauterine transmission and the need for clinicians to promptly test neonates born to SARS-CoV-2 positive mothers at delivery for COVID-19. It is imperative to establish the real risk of intrauterine transmission and to develop appropriate preventive and treatment strategies.